Novel Synthesis of 4,5-Unsubstituted 2,3-Dihydroisoxazoles from 5-Acetoxyisoxazolidines - Fischer, Róbert; Lackovičová, Daniela; Fišera, Lubor (Synthesis, 2012)
A new synthetic method for the preparation of 4,5-unsubstituted 2,3-dihydroisoxazoles from readily available 5-acetoxyisoxazolidines is presented. Elimination reactions are carried out in anhydrous N-methylpyrrolidin-2-one (NMP) with a catalytic amount of trimethylsilyl triflate in the presence of N,O-bis(trimethylsilyl)trifluoroacetamide (BSTFA) and provide the 2,3-dihydroisoxazoles in very good yields. The nature of the silylating agent plays a very important role in elimination process. Anhydrous reaction conditions are required, while trimethylsilanol, the product of trimethylsilyl triflate and N,O-bis(trimethylsilyl)trifluoroacetamide hydrolysis, can initiate reactions leading to deacetylation, giving side products and thus decreasing the total yield of the elimination.
Keywords: elimination; Lewis acids; cycloaddition; nitrones; 2,3-dihydroisoxazoles